Metamagnetism in nanosheets of Co-II-MOF with T-N at 26 K and a giant hysteretic effect at 5 K - Gupta, Kriti; Dadwal, Arun; Rana, Shammi; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2018)
Herein, we have synthesized at room-temperature two-dimensional nanosheets of a MOF comprised of cobalt(II) ion with benzenedicarboxylic acid ligand, which exhibited unusual magnetic properties. Direct-current magnetic susceptibility revealed an anti-ferromagnetic (AFM) transition at 26 K (Neel temperature, T-N) followed by a canting of the spin moments along with the concomitant appearance of a sigmoidal-shaped magnetization versus field (M-H) curve at 15 K. Such a canted AFM ordering led to nonzero remnant magnetization with a remarkably high coercive field of similar to 10 kOe at 5 K. Metamagnetism was further: substantiated by the alternating-current magnetic susceptibility measurements.

Exploring magnetic XY behavior in a quasi-2D anisotropic triangular lattice of Cu(II) by functionalized graphene - Gupta, Kriti; Dadwal, Arun; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2020)
Study on magnetism in two-dimensional (2D) spin-lattices is advancing rapidly. In this work, phase-pure botallackite (Bo) (Cu-2(OH)(3)Br), a quasi-2D S = 1/2 anisotropic triangular spin-lattice is stabilized over 2D reduced graphene oxide (rGO) nanosheets via simple oxidation-reduction reaction chemistry. In comparison to polycrystalline Bo, such an anchoring resulted in the oriented growth of Bo crystallites in the Bo-rGO system. The Bo-rGO nanocomposite was found to be magnetically active with a Neel transition at 8.9 K, crossing over to possible XY anisotropy at similar to 5 K-as revealed by complementary dc and ac susceptibility measurements-an unprecedented observation in the field assigned to an interfacial effect. This work demonstrates the potential usage of nonmagnetic 2D functionalized graphene to significantly modulate the magnetic properties of 2D spin-lattices.

Possible electron doping of geometrically perfect spin-1/2 kagome-lattice barlowite by reduced graphene oxide - Gupta, Kriti; Ninawe, Pranay; Jain, Anil; Dadwal, Arun; Anas, M.; Malik, V. K.; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Physical Review B, 2021)
Doping of quantum spin liquid (QSL) insulators by electron or hole leads to intriguing phase transitions to metallic and superconducting states. The barlowite family with geometrically perfect S = 1/2 kagome planes and tunable interkagome coupling is an emerging platform to realize spin-ordered, valence bond crystal, QSL states. Theoretical investigations on electron doping revealed localized states in the band gap of barlowite unlike metallicity in cuprate (Nd2CuO4). We present successful anchoring of phase-pure barlowite crystallites onto reduced graphene oxide (rGO). The resulting barlowite-rGO system was found to be an electrical semiconductor with Arrhenius activation energy of 0.07 eV. Semiconducting properties of the barlowite-rGO system were further modulated with retention of structural integrity. We have attributed such a transformation of electrical transport response to plausible electron doping thereby making charge-doping experiments on barlowite and its analogs propitious.

Intertwining of localized (d) and delocalized (π) spins in magnetically frustrated two-dimensional metal-organic frameworks - Ugale, Ajay; Ninawe, Pranay; Jain, Anil; Sangole, Mayur; Mandal, Rimpa; Singh, Kirandeep; Ballav, Nirmalya (Inorganic Chemistry, 2024)
Two-dimensional metal-organic frameworks (2D MOFs) are emerging as a new class of multifunctional materials for diversified applications, although magnetic properties have not been widely explored. The metal ions and organic ligands in some of the 2D MOFs are arranged in the well-known Kagome lattice, leading to geometric spin frustration. Hence, such systems could be the potential candidates to exhibit an exotic quantum spin liquid (QSL) state, as was observed in Cu-3(HHTP)(2) (HHTP = hexahydroxytriphenylene), with no magnetic transition down to 38 mK. Hereto, we have investigated the spin intertwining in a bimetallic 2D MOF system, M-3(HHTP)(2) (M = Cu/Zn)(,) arising from the localized (d-electron) and delocalized (pi-electron) S = 1/2 spins from the Cu(II) ions and the HHTP radicals, respectively. The origin of the spin frustration (down to 5K) was critically examined by varying the metal composition in bimetallic systems, CuxZn3-x(HHTP)(2) (x = 1, 1.5, 2), containing both S = 1/2 and S = 0 spins. Additionally, to gain a deeper understanding, we studied the spin interaction in the pristine Zn-3(HHTP)(2) system containing only S = 0 Zn(II) ions. In view of the quantitative estimate of the localized and delocalized spins, the d-pi spin correlation appears essential in understanding the unusual magnetic and/or other physical properties of such hybrid organic-inorganic 2D crystalline solids

Robust spin liquidity in 2D metal-organic framework Cu3 (HHTP)2 with S=1/2 kagome lattice - Ninawe, Pranay; Jain, Anil; Sangole, Mayur; Anas, Mohd; Ugale, Ajay; Malik, Vivek K.; Yusuf, Seikh M.; Singh, Kirandeep; Ballav, Nirmalya (Chemistry- a european journal, 2024)
On one hand electron or hole doping of quantum spin liquid (QSL) may unlock high-temperature superconductivity and on the other hand it can disrupt the spin liquidity, giving rise to a magnetically ordered ground state. Recently, a 2D MOF, Cu-3(HHTP)(2) (HHTP - 2,3,6,7,10,11-hexahydroxytriphenylene), containing Cu(II) S = 1/2 frustrated spins in the Kagome lattice is emerging as a promising QSL candidate. Herein, we present an elegant in situ redox-chemistry strategy of anchoring Cu-3(HHTP)(2) crystallites onto diamagnetic reduced graphene oxide (rGO) sheets, resulting in the formation of electron-doped Cu-3(HHTP)(2)-rGO composite which exhibited a characteristic semiconducting behavior (5 K to 300 K) with high electrical conductivity of 70 S . m(-1) and a carrier density of similar to 1.1 x 10(18) cm(-3) at 300 K. Remarkably, no magnetic transition in the Cu-3(HHTP)(2)-rGO composite was observed down to 1.5 K endorsing the robust spin liquidity of the 2D MOF Cu-3(HHTP)(2). Specific heat capacity measurements led to the estimation of the residual entropy values of 28 % and 34 % of the theoretically expected value for the pristine Cu-3(HHTP)(2) and Cu-3(HHTP)(2)-rGO composite, establishing the presence of strong quantum fluctuations down to 1.5 K (two times smaller than the value of the exchange interaction J).
Keywords: 2D Metal-organic Framework; Electron doping; Reduced graphene oxide; Spin Liquid; Spin-frustration